Bone regeneration by means of a three‐dimensional printed scaffold in a rat cranial defect. (26th November 2017) - Kwon, Doo Yeon; Park, Ji Hoon; Jang, So Hee; Park, Joon Yeong; Jang, Ju Woong; Min, Byoung Hyun; Kim, Wan‐Doo; Lee, Hai Bang; Lee, Junhee; Kim, Moon Suk
Abstract: Recently, computer‐designed three‐dimensional (3D) printing techniques have emerged as an active research area with almost unlimited possibilities. In this study, we used a computer‐designed 3D scaffold to drive new bone formation in a bone defect. Poly‐L‐lactide (PLLA) and bioactive β‐tricalcium phosphate (TCP) were simply mixed to prepare ink. PLLA + TCP showed good printability from the micronozzle and solidification within few seconds, indicating that it was indeed printable ink for layer‐by‐layer printing. In the images, TCP on the surface of (and/or inside) PLLA in the printed PLLA + TCP scaffold looked dispersed. MG‐63 cells (human osteoblastoma) adhered to and proliferated well on the printed PLLA + TCP scaffold. To assess new bone formation in vivo, the printed PLLA + TCP scaffold was implanted into a full‐thickness cranial bone defect in rats. The new bone formation was monitored by microcomputed tomography and histological analysis of the in vivo PLLA + TCP scaffold with or without MG‐63 cells. The bone defect was gradually spontaneously replaced with new bone tissues when we used both bioactive TCP and MG‐63 cells in the PLLA scaffold. Bone formation driven by the PLLA + TCP30 scaffold with MG‐63 cells was significantly greater than that in other experimental groups. Furthermore, the PLLA + TCP scaffold gradually degraded and matched well the extent of the gradual new bone formation on microcomputed tomography. In conclusion, the printed PLLA + TCP scaffold effectively supports new bone formation in a cranial bone defect.